2019
DOI: 10.1177/2192568219828727
|View full text |Cite
|
Sign up to set email alerts
|

Primary Bone Tumor of the Spine—An Evolving Field: What a General Spine Surgeon Should Know

Abstract: Study Design: A narrative review of the literature. Objective: This article reviews the general principles of treatment and investigation for primary bone tumors of the spine. Furthermore, it explores the emerging alternatives. Methods: A review was performed using Medline, Embase, and Cochrane databases. Results: Primary bone tumors of the spine are rare entities that general spine surgeons may encounter only a few times in their career. The treatment algorithm of these complex tumors is filled with nuances a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 62 publications
1
8
0
2
Order By: Relevance
“…Складывается тревожная ситуация. В арсенале спинальных хирургов содержатся алгоритмы и классификации для первичных и вторичных опухолей позвоночника [3,4,5], инфекционных спондилитов [6], патологических переломов на фоне остеопороза [7] и прочие специфические гайдлайны. Но у нас нет адекватных инструментов для комплексной оценки деструктивного процесса как синдрома.…”
Section: современное состояние проблемыunclassified
“…Складывается тревожная ситуация. В арсенале спинальных хирургов содержатся алгоритмы и классификации для первичных и вторичных опухолей позвоночника [3,4,5], инфекционных спондилитов [6], патологических переломов на фоне остеопороза [7] и прочие специфические гайдлайны. Но у нас нет адекватных инструментов для комплексной оценки деструктивного процесса как синдрома.…”
Section: современное состояние проблемыunclassified
“…However the SINS score is only partially helpful for surgeon as a treatment guide [8]: there is a large grey zone of "potentially unstable" (SINS 7 to 12), were spine surgeons currently must rely on their own experience to determine whether instability is present in the setting of spinal neoplasia and surgery is urgently indicated. A recent review [9] confirmed that the recommendations for treating the primary bone tumors are based on moderate quality evidence and expert opinions.…”
Section: Introductionmentioning
confidence: 99%
“…The spine is a complex skeletal anatomic structure involved in weight bearing, shock absorption, and motion. Tumors involving the spine, whether primary or metastatic, may cause severe back pain, limb numbness, weakness and/or paralysis[ 5 ]. Total en bloc resection of spinal tumors is the most direct and effective way to relieve symptoms, recover function, and prevent tumor progression[ 6 ].…”
Section: Introductionmentioning
confidence: 99%